The economics of transition - Gaĭdar, E. T. (Egor Timurovich) (MIT Press, 2003)
Russian analysts discuss postcommunist economic transformation. The end of the Cold War saw an unprecedented number of countries changing economic policies at the same time. One result has been the emergence of a new field of economics, postcommunist transformation theory. Written by prominent Russian analysts, the essays in this book discuss the economic policy problems that confront postcommunist countries. Most chapters focus on liberalization of the exchange rate and trade system, macroeconomic stabilization, and institutional reform. They also look at various policy options that have been pursued and their results. Underlying the book is the assumption that the transition to a market economy is both irreversible and the best path to sustained growth in Russia.